(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: CT-scan can detect hepatocelluar carcinoma among the patients. Objective: The purpose of the present study was to see the pattern of hepatocelluar carcinoma among the patients attended at a tertiary care hospital in Dhaka city. Methodology: This cross-sectional study was carried out in the Department of Radiology and Imaging at Dhaka Medical College, Dhaka and Banghabandhu Sheikh Mujib Medical University, Dhaka from January 2007 to May 2008 for a period of around one and half year. All the patients presented with hepatocellular carcinoma at the age group of more than 20 years with both sexes were selected as study population. The patients were undergone CT-scan examination and the confirmation of tumor was performed by histopathological examination. Result: A total number of 50 patients were recruited in this study after fulfilling the inclusion and exclusion criteria. The sensitivity, specificity and accuracy of CT-scan in detecting hepatocellular carcinoma was seen to be 66%, 92% and 72% respectively. The PPV and NPV were 96.15% (95% CI 79.06% to 99.40%) and 45.83% (95% CI 34.53% to 57.58%) respectively. However, the Positive Likelihood Ratio and Negative Likelihood Ratio were 7.89 (95% CI 1.19 to 52.28) and 0.37(95% CI 0.23 to 0.60). Conclusion: In conclusion CT-scan is a good diagnostic tool for the detection of hepatocellular carcinoma. Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 133-136